Vocational expertise is agency - Maria C. Johansson (Discover Education)
Abstract Vocational education and training (VET) suffers from declining interest and is often perceived as non-attractive. This view may deprive young people of a potentially rewarding and satisfying career. There are also a variety of challenges in vocational didactics and in the cooperation between education systems and trades. In this article, it is argued that one reason for this is epistemological and that there is a lack of a proper recognition of vocational expertise. Thus, the aim is to contribute to an exploration of vocational expertise and its connection to knowledge, a vocation, agency and discuss how this becomes relevant for VET. The empirical material consists of earlier video-recorded workplace studies which are revisited and reanalysed. Here importance is given to tacit knowledge and practical wisdom. The analysis is underpinned by knowledge and practice theories, and it is concluded that vocational expertise could be defined as a specific kind of knowing that is cultivated through the acquaintance with a vocational practice in which the expert has the agency. This conclusion is supported by a conceptualisation of a vocation as a practice of social, cultural, and historical value for its practitioners as well as for the society. In other words, agency is a given and needs to be embedded and recognised in expertise. Finally, there is a discussion of possible implications for VET.